AB0234 Differential Relative Contribution of Individual Components on DAS28 over Time. an Analysis from the Prospective, Observational Registry, Biotrac. (10th June 2014) - Choquette, D.; Sholter, D.; Fortin, I.; Starr, M.; Thorne, C.; Baker, M.; Arendse, R.; Baer, P.; Zummer, M.; Rodrigues, J.; Sheriff, M.; Rampakakis, E.; et al.
Abstract : Background: DAS28 is an important outcome for clinical research and practice assisting with therapeutic decisions. The main contributors to DAS28 are joint tenderness and acute-phase reactants. A simulation analysis showed that, due to its logarithmic transformation in the DAS28 formula, the ESR contribution is greater in the lower than in the higher DAS28 range. Objectives: This analysis assessed the relative contribution of individual DAS28 components and examined its clinimetric properties in rheumatoid arthritis (RA) patients treated with infliximab in a Canadian real-world setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with infliximab or golimumab as first biologics or after treatment with a biologic for <6 months (M). RA patients treated with infliximab between 2002-2012 and with ≤60M of follow-up were included. The association between treatment duration and parameter improvement was assessed using linear regression. Slope correlation was assessed with the Pearson's correlation coefficient. Results: 832 patients evaluated over 4, 002 visits were included. Longer treatment duration was associated with significant (P<0.001) improvements in DAS28, TJC28, SJC28, PtGA, ESR, and CRP. Correlation analysis of the rate of change over time showed a high correlation (0.7-0.9) of DAS28 with TJC28, SJC28, and PtGA but low correlation with ESR (r=0.418) and CRP (r=0.411). Overall, the relative contribution of TJC28, SJC28, PtGA, and ESR in DAS28-ESR was 22%, 9%, 12%, and 57%, respectively. For DAS28-CRP, the relative TJC28, SJC28, PtGA, and CRP contributions were 25%, 10%, 12%, and 20%. Over 60M of treatment, the mean relative contribution of TJC28 (M0:31%, M60:17%), SJC28 (M0:15%, M60:5%), and PtGA (M0:15%, M60:9%) significantly (P<0.001) decreased whereas the weight of ESR contribution increased (M0:39%, M60:69%). Similar results were obtained with DAS28-CRP although the CRP contribution was lower compared to ESR. Increased DAS28-ESR was associated with higher relative contributions (per unit of DAS28-ESR increase) of TJC28 [parameter estimate (B) =5.3], SJC28 (B=2.1), and PtGA (B=0.7) but lower ESR contribution (B=-8.1). Similarly, increased DAS28-CRP was associated with lower relative CRP contribution (B=-2.0). Conclusions: This analysis shows that TJC28 and acute-phase reactants have a greater weight than SJC28 and PtGA within DAS28. Furthermore, the relative contribution of acute-phase reactants is greater with lower DAS28, due to their logarithmic nature. These findings suggest that biologic variability and variability in laboratory techniques may have significant impact on classifying remission or DAS28 changes among patients with low DAS28 and on therapeutic plan changes. Disclosure of Interest: D. Choquette: None declared, D. Sholter: None declared, I. Fortin: None declared, M. Starr: None declared, C. Thorne: None declared, M. Baker: None declared, R. Arendse: None declared, P. Baer: None declared, M. Zummer: None declared, J. Rodrigues: None declared, M. Sheriff: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen, A. Lehman Employee of: Janssen, S. Otawa Employee of: Janssen, M. Shawi Employee of: Janssen DOI: 10.1136/annrheumdis-2014-eular.2379